Water scarcity, data scarcity and the Budyko curve—An application in the Lower Jordan River Basin - Lange, J. (2020)
Water scarcity and data scarcity are two of the main challenges for water management in the study region, therefore, all possible information should be extracted from existing data. In this context, the Budyko framework offers possibilities not yet sufficiently explored for evaluating the water-energy balance and estimating water availabilities. In this study, we applied a parametric Budyko type equation to the Lower Jordan River basin and compared data from global products, output of the hydrological model TRAIN-ZIN as well as values from literature. The curve shape parameters of the Budyko type curve fitted on different temporal and spatial scales were used to estimate renewable water resources with publicly available data for three subbasins.